Squamous cell lung carcinoma presenting as melena: a case report and review of the literature - Azar, Ibrahim (Rare Tumors, 2017)
Lung cancer has a predilection to widely metastasize to the liver, bone, brain and adrenal glands. Metastasis of primary lung tumors to the stomach is infrequent, with only sporadic cases reported. Most cases are asymptomatic and diagnosed post-mortem on autopsy. The incidence of symptomatic gastrointestinal metastases is extremely rare. Herein, we describe a case of gastric metastasis by squamous cell lung carcinoma, presenting as melena and diagnosed by esophagogastroduodenoscopy. To the best of our knowledge, only twenty other cases in the English literature have reported symptomatic gastric metastasis of lung cancer diagnosed by endoscopic biopsy. A brief review of the literature shows gastric metastasis of lung cancer to have a predilection to occur most frequently in male smokers with the most common type of tumor likely to be squamous cell carcinoma.